Description Of Sports Behavior In Diabetes Mellitus Patients At UPT Puskesmas Delitua Year 2021 - Mestiana Br. Karo; Lindawati Tampubolon; Mardiati Barus; Annastasya Paulina Br. Ginting (Jurnal EduHealth, 2022)
Diabetes Mellitus (DM) is a chronic metabolic disorder that is better known as the silent killer of humans. Often humans do not realize that the person has diabetes, and often experience delays in handling it so that many complications occur. Diabetes is also known as the "Mother of Disease" because it is the mother or mother of other diseases such as hypertension, heart disease, stroke, heart failure. kidney and blindness. If left uncontrolled, this disease can cause other complications that endanger health. The recommended exercise for diabetics is low impact and rhythmic aerobic exercise such as gymnastics, jogging, swimming and riding a bicycle. The purpose of the study was to determine the description of sports behavior of people with diabetes mellitus at UPT Puskesmas Delitua 2021. The research method was a descriptive study of a sample of 50 respondents using a purposive sampling technique. The instrument or tool used was a questionnaire of 15 questions of sports behavior. The results of the study can be concluded that the female gender is more likely to be diabetic mellitus sufferers obtained as many as 29 respondents (58.0%), the majority age is in the age range of 56-65 years as many as 20 people (40.0%), the majority do not work as much as 27 people (54.0%) and 41 respondents (82.0%). Suggestion: It is hoped that people with diabetes mellitus can improve their exercise behavior.